Policing in Cool and Hot Climates: Legitimacy, Power and the Rise and Fall of Mass Stop and Search in Scotland. (7th April 2016) - Murray, Kath; Harkin, Diarmaid
Abstract: Prior to the amalgamation of Scotland's eight police forces into Police Scotland in 2013 by the Scottish National Party government, Scottish policing generally enjoyed a 'cool' political climate, with low scrutiny and minimal political engagement. This paper argues these conditions hindered the critical interrogation of Scottish policing, allowing a policy of unregulated and unfettered stop and search to flourish unchallenged for two decades. We then show how this policy was swiftly dismantled in the 'heated' environment that followed centralization, a move that gave rise to the unprecedented scrutiny of Scottish policing by media and political commentators. The analysis suggests that the legitimacy and reputation of the police may owe a debt to political environments that encourage either 'soft' or 'hard' analysis. Also, that more heated political environments, often disparaged by academics and criminal justice practitioners, can drive accountability and contribute to more progressive outcomes.